Rancang Bangun Aplikasi Blood Bank Berbasis Web - Sidratulmunti, Novi Yona; Fiatno, Aris (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The Indonesian Red Cross Society (PMI) has a problem. This means blood units are still using manual processing of donor data, degrading their service to the community. Currently, information systems are evolving with the development of information technology, which has been proven to be very fast and play a role in various activities. Blood donation is one of the activities that can utilize the information system. The research method used in this study is Waterfall method and the system he developed using Laravel Framework, Bootstrap and MySQL database. The outcome of this study is an information system that can support blood donor units and the general public in the systematic management of donor data to obtain information on the availability of blood supplies at Palang Merh Indonesia (PMI) of Regency . Website